TINJAUAN PENGGUNAAN ABU BATU DAN ABU VULKANIK SEBAGAI FILLER TERHADAP DURABILITAS ASPHALT CONCRETE-WEARING COURSE (AC – WC) - Hadi Ali (UNIVERSITAS LAMPUNG, 2013)
Filler is component of pavement construction. The little prosentase of filler in the mixture has bigeffect in characters marshall also be mixture performance towards traffic load. The pavementconstruction in this research is asphalt concrete - wearing course (ac-wc), by using vulcanic ashand stone ash as filler in refusal density. In asphalt optimum content that is 6,00 % to filler ofstone ash and 5,9 % to filler of vulcanic ash, in refusal density test 2x400 collision, fulfil spesifica-tion and both types of collision be correlate of marshall parameter with longly soaking 0, 1, 2,and 3 days. The result that got after soaking, pavement structural with filler of vulcanic ash hasstability 1084,307 kg and flow 3,55 mm, while a with filler of stone ash has stability 1077,842 kgand flow 3,6 mm. Test of durability that mixture with filler of vulcanic ash has value better from instone ash, the Retained stability index of mixture with filler of vulcanic ash has prosentase99,08262 %, while in filler of stone ash 98,84916 %.